2016
DOI: 10.1093/jamia/ocw156
|View full text |Cite
|
Sign up to set email alerts
|

De-identification of patient notes with recurrent neural networks

Abstract: Our findings support the use of ANNs for de-identification of patient notes, as they show better performance than previously published systems while requiring no manual feature engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
310
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(317 citation statements)
references
References 32 publications
7
310
0
Order By: Relevance
“…[4,14] In the recent years, there has been an increase in the use of deep neural networks for a variety of NLP tasks, including NER. [5,6,7] Pre-trained word embeddings [8,9,15] have been used in traditional ML methods [16,17] and in neural networks, where Deconourt et al [18] has achieved better performance than previously published systems in de-identification of patient notes. Finally, Lee et al [19] have shown that featureaugmented neural networks can use a combination of word embeddings and domain-specific features to further improve the performance in de-identification of patient notes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,14] In the recent years, there has been an increase in the use of deep neural networks for a variety of NLP tasks, including NER. [5,6,7] Pre-trained word embeddings [8,9,15] have been used in traditional ML methods [16,17] and in neural networks, where Deconourt et al [18] has achieved better performance than previously published systems in de-identification of patient notes. Finally, Lee et al [19] have shown that featureaugmented neural networks can use a combination of word embeddings and domain-specific features to further improve the performance in de-identification of patient notes.…”
Section: Related Workmentioning
confidence: 99%
“…However, it has been proved that pre-trained word embeddings can improve the performance of the network. [5,12,18,19] In this section, we present the pre-trained embeddings employed in lieu of the random assignments.…”
Section: Word Featuresmentioning
confidence: 99%
“…However, permissions to access other's data in a central warehouse are still cumbersome to obtain and de-identification efforts are either costly, error prone, or ineffective [6,7]. Human-based de-identification effort costs over 5,000 hours and US$500,000 on Medical Information Mart for Intensive Care III (MIMIC-III) dataset [8], which contains only about 50,000 patient visits and 100 million words [9]. and produces error recall ranging from 0.63 to 0.94 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Machine-assisted de-identification shows varying results from time savings of 13.85-21.5% to results showing no improvement in either quality or time saved [11]. Machine learning algorithm-based automated deidentification can be very useful, but state-of-the-art deep learning-based de-identification models for unstructured data is still incapable of reaching to the level of privacy protection set by HIPAA safe harbor, which has roughly a 0.013% re-identification rate [9,12]. In the biomedical community, there is an urgent need for developing a new method to share information learned from local sources to generalize and scale up research effort.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has been applying neural network methods to various clinical NLP tasks, such as named entity recognition (NER) [19,20], de-identification [21] and sentiment analysis [22][23][24]. Neural network methods are advantageous because they were shown to save significant time on task specific features extraction, achieved high performance, and are scalable to large applications [25].…”
Section: Introductionmentioning
confidence: 99%